The knowledge‐based economy in Lithuania: Analysis of tendencies - Ginevičius, Romualdas; Korsakiene, Renata (Journal of Business Economics and Management, 2005)
The purpose of this paper is to analyse the tendencies of knowledge‐based economy in Lithuania by looking at a knowledge economy’s major dimensions ‐ the structure of economic activity and the infrastructure of knowledge economy. The knowledge‐based economy is the dominant post‐industrial economic development paradigm. The emergence of this paradigm in the 1980s created preconditions to emphasize the role of knowledge creation and distribution as the primary driver in the process of economic development and growth, the distribution of income, development of knowledge‐based networks among firms and the interface between government, business and citizens in the advanced economies. First published online: 14 Oct 2010